2020
DOI: 10.3390/ijms21238896
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Stimulation Combined with Triple Gene Therapy for Spinal Cord Injury Treatment

Abstract: The translation of new therapies for spinal cord injury to clinical trials can be facilitated with large animal models close in morpho-physiological scale to humans. Here, we report functional restoration and morphological reorganization after spinal contusion in pigs, following a combined treatment of locomotor training facilitated with epidural electrical stimulation (EES) and cell-mediated triple gene therapy with umbilical cord blood mononuclear cells overexpressing recombinant vascular endothelial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 80 publications
1
24
0
Order By: Relevance
“…Hind limb skeletal muscle contraction and the appearance of a consistent hematoma at the site exposed to the metal rod confirmed the onset of SCI. Moderate contusion injury in mini pigs has demonstrated consistent morphological and behavioural changes across our previous studies [ 28 , 29 , 32 , 36 ].…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations
“…Hind limb skeletal muscle contraction and the appearance of a consistent hematoma at the site exposed to the metal rod confirmed the onset of SCI. Moderate contusion injury in mini pigs has demonstrated consistent morphological and behavioural changes across our previous studies [ 28 , 29 , 32 , 36 ].…”
Section: Methodssupporting
confidence: 80%
“…In our previous study, we reported the procedure of stimulating electrodes implantation at the C5 and L2 spinal cord segments in mini-pigs with subsequent spinal contusion at the Th9 segment [ 29 ]. It was shown that sublesional EES at L2 activates central pattern generators and facilitates hind limb movements on a treadmill.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have attempted to identify new treatments, such as drug administration, surgical decompression, hypothermia, and stem cells therapies, which could promote nerve cell regeneration, repair damaged parts, reduce the metabolic rate, and suppress acute inflammatory processes (to protect central nerve tissue from continued injury following traumatic damage) [5,6]. Recently, new therapeutic methods, such as cell/gene therapy, motor exercises, electrical stimulation, electrochemical neuromodulation therapy, and stem cell-based therapies, have been used, alone or in a combinatory approach, to achieve successful SCI therapy [7].…”
Section: Introductionmentioning
confidence: 99%